Silk fibroin hydrogel containing bivalent bioactive metal ions and preparation method thereof
By chelating crosslinking and β-sheet crosslinking of divalent metal ions with silk fibroin without adjusting the pH value and adding a gel-forming agent, the rapid gel-forming of silk fibroin hydrogels is achieved, solving the problems of long glue-forming time and difficult to ensure biosafety in the prior art, and improving production efficiency and biosafety.
Patent Information
- Application Number
- CN202411791121.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to efficiently prepare silk fibroprotein hydrogel without adjusting the pH value and adding gel-forming agents, and the gel-forming time is long, making it difficult to ensure biosafety and production efficiency.
By dissolving the degummed silk in water dissolved with divalent metal salts, dialysis and shear force are applied, the chelating crosslinking of the hydrophilic segment of the silk fibroin and the divalent metal ions, and the β-sheet crosslinking of the hydrophobic segments are achieved, rapid gel formation is achieved.
The rapid gel formation of silk fibroprotein hydrogel is achieved, with good operability, biosafety and versatility, avoiding pH adjustment and the use of gel forming agents, and improving production efficiency.
Smart Images

Figure CN119529323A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tissue repair and medical dressings, and in particular to a silk fibroin hydrogel containing divalent bioactive metal ions and a preparation method thereof. Background Art
[0002] Silk is an animal protein fiber, which is mainly composed of fibroin and sericin, of which fibroin accounts for about 70%-80%. At the same time, fibroin is non-toxic and non-allergenic in the human body, has good biocompatibility, and is a highly potential biomedical material. At present, fibroin is mainly extracted from natural silk. The general process includes degumming, hydrolysis, dialysis and filtration. The degumming process is to use protease or chemical degumming agent to remove sericin from silk and retain fibroin. The hydrolysis process is to hydrolyze silk fibroin with acid, alkali or neutral inorganic salt.
[0003] Chinese invention CN106866996A discloses a method for rapidly preparing silk fibroin gel. After adjusting the pH of the silk fibroin solution to acidity, a weak electric field is used. Although the silk fibroin quickly forms a gel, the pH needs to be adjusted to develop it into a medical gel dressing. Chinese invention CN110064077A discloses a silk fibroin hydrogel for treating intrauterine adhesions. The preparation method forms a gel by adding a poloxamer chemical crosslinking agent, but the biocompatibility of the addition of substances such as poloxamer remains to be confirmed. ; Chinese invention CN103289107A discloses a preparation method and application of an injectable silk fibroin in situ gel, in which polyethylene glycol, propylene glycol, etc. are added to induce silk fibroin to gel. Although the gel can be formed in 10 minutes, these inducers are difficult to remove and the safety is difficult to ensure; Chinese invention CN115282324A discloses a silk fibroin hydrogel dressing and its preparation method and application, in which the silk fibroin is gelled by swirl shear and temperature induction. The gelling time of heat treatment is 5 to 18 hours, and the gelling time is long.
[0004] Therefore, a method for efficiently preparing silk fibroin hydrogel without adjusting pH and introducing a gelling agent is needed.
[0005] As a biomedical product, how to ensure its biosafety while producing efficiently is the core element of technological development. The above-mentioned silk fibroin gelling method cannot be both biosafe and efficient. Although adding gelling agent can shorten the gelling time of silk fibroin, the problem of residual gelling agent cannot ensure biosafety; if no gelling agent is added, the gelling time of silk fibroin will be increased, reducing production efficiency. In addition, how to enrich the biological functions of silk fibroin hydrogel to meet the repair requirements of tissues in different parts of the human body is also one of the development directions of personalized functional biomaterials in the future. Studies have shown that divalent bioactive metal ions, such as magnesium ions, strontium ions, zinc ions, calcium ions, copper ions, etc., have outstanding abilities in promoting angiogenesis, repairing soft and hard tissues, and anti-inflammatory and antioxidant effects. Its chelation with the hydrophilic chain segment of silk fibroin can not only accelerate the gelling speed of silk fibroin, but also give silk fibroin materials richer biological functions.
[0006] Therefore, the present invention has great significance for developing rapid gelling technology of silk fibroin and enriching the biological functions of silk fibroin without adding a gelling agent. The silk fibroin gel prepared by the present invention does not need to adjust the pH and does not add a gelling agent. It effectively combines the two cross-linking mechanisms of the hydrophilic segments of the silk fibroin chelated by divalent metal ions and the β-folding cross-linking of the hydrophobic segments of the silk fibroin promoted by high shear. It not only develops rapid gelling technology, but also can compound one or more divalent metal ions according to the intended use. It has good operability, biosafety and versatility, and can be applied to the fields of soft and hard tissue repair and medical dressings. Summary of the invention
[0007] The purpose of the present invention is to provide a silk fibroin hydrogel containing divalent bioactive metal ions and an efficient and green preparation method thereof, which does not require pH adjustment and gelling agent addition during the preparation process, and the prepared silk fibroin hydrogel has good operability, biosafety and multifunctionality.
[0008] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a silk fibroin hydrogel containing divalent bioactive metal ions, comprising the following steps: S1: dissolving degummed silk with a solvent to prepare a silk fibroin stock solution; S2: dialyzing the silk fibroin stock solution in water dissolved with a divalent metal salt to obtain a silk fibroin composite solution; S3: heat-insulating the silk fibroin composite, applying a shear force, and incubating to obtain a silk fibroin hydrogel containing metal ions.
[0009] The beneficial effects of the preparation method of the silk fibroin hydrogel provided by the present invention are as follows: the preparation method of the silk fibroin hydrogel is simple, and during the preparation process, it is not necessary to adjust the pH value or add a gelling agent. The silk fibroin aqueous solution is rapidly gelled by utilizing two cross-linking mechanisms: divalent metal ion chelation to cross-link the hydrophilic segments of the silk fibroin and shear force to promote the β-folding cross-linking of the hydrophobic segments of the silk fibroin. The method has good operability, biosafety and multifunctionality.
[0010] Preferably, the dissolving agent includes calcium chloride, ethanol and water, or the dissolving agent includes calcium chloride and formic acid solution; the mass fraction of calcium chloride in the dissolving agent composed of calcium chloride, ethanol and water is 30% to 40%, the mass fraction of ethanol is 20% to 30%, and the rest is water; the mass volume fraction of calcium chloride in the formic acid solution in the dissolving agent composed of calcium chloride and formic acid is 5% to 8%. Its beneficial effect is that it can accelerate the dissolution and reduce the time for the silk fibroin to be completely dissolved.
[0011] Preferably, the dissolution temperature is 60-90° C., and the dissolution time is 2-5 hours.
[0012] Preferably, the molecular weight cutoff of the dialysis bag used for dialysis is greater than 10KDa, the number of dialysis is 3 to 9 times, and the duration of each dialysis is 2 to 4 hours. The beneficial effect is that the molecular weight cutoff of the dialysis bag is greater than 10KDa, so that the silk fibroin molecules will not be retained by the dialysis bag.
[0013] Preferably, the divalent metal salt refers to a water-soluble divalent metal salt, which includes magnesium, zinc, calcium, copper, strontium and iron. The beneficial effect is that the divalent metal salt can chelate the hydrophilic chain segment of silk fibroin and accelerate the gelation of silk fibroin.
[0014] Preferably, before S3, the silk fibroin solution is diluted or concentrated to adjust the concentration to 0.1-10.0 wt %.
[0015] Preferably, the dilution method includes dilution with water, and the concentration method includes ultrafiltration, PEG solution dialysis or heating volatilization.
[0016] Preferably, the shear force is applied by an emulsifier, and the emulsifier can drive the silk fibroin solution to rotate. The rotation speed of the emulsifier is 8000-30000 rpm, and the rotation time is 30 s-5 min.
[0017] Preferably, the incubation temperature is 40-80° C., and the incubation time for gelation is 0.5-3 h.
[0018] In a second aspect, an embodiment of the present invention provides a silk fibroin hydrogel containing divalent metal ions, which is prepared by the above-mentioned preparation method.
[0019] The beneficial effects of the present invention are that the prepared silk fibroin hydrogel has good operability, biosafety and multifunctionality. In addition, the preparation method of the silk fibroin hydrogel is simple, the gelling speed is fast, and no gelling agent needs to be added and the pH value needs to be adjusted during the preparation process, thereby improving production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The present invention is a flow chart of the preparation method of the embodiment; Figure 2 This is a graph showing changes in calcium ion concentration with the number of dialysis sessions according to an embodiment of the present invention; Figure 3 This is a graph showing the effect of calcium ion concentration on the gelation time of silk fibroin in an embodiment of the present invention; Figure 4 These are effect diagrams of silk fibroin solution and silk fibroin gel according to embodiments of the present invention. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the usual meanings understood by people with general skills in the field to which the present invention belongs. "Including" and similar words used in this article mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. Unless otherwise specified, the "connection" described in this article can be a direct connection or an indirect connection, that is, connected through an intermediate.
[0022] In view of the problems existing in the prior art, an embodiment of the present invention provides a method for preparing a silk fibroin hydrogel, comprising the following steps: S1: dissolving degummed silk with a dissolving agent to prepare a silk fibroin stock solution; S2: dialyzing the silk fibroin stock solution in water dissolved with a divalent metal salt to obtain a silk fibroin composite solution; S3: applying shear force to the silk fibroin composite after heat preservation treatment, and incubating to obtain a silk fibroin hydrogel containing metal ions.
[0023] In this embodiment, the degummed silk is obtained by putting silk into a sodium carbonate solution for degumming. After the degummed silk is treated with a solvent, it is dialyzed, shear force is applied, and incubated to gel to obtain a silk fibroin hydrogel. This preparation method is simple, and there is no need to adjust the pH value or add a gelling agent during the preparation process. The two cross-linking mechanisms of calcium ions in the solvent to chelate and cross-link the hydrophilic segments of the silk fibroin and shear force to promote the β-folding cross-linking of the hydrophobic segments of the silk fibroin make the silk fibroin aqueous solution quickly gel, and the method has good operability and biosafety.
[0024] In some embodiments, the dissolving agent includes calcium chloride, ethanol and water, or the dissolving agent includes calcium chloride and formic acid solution; the mass fraction of calcium chloride in the dissolving agent composed of calcium chloride, ethanol and water is 30%~40%, the mass fraction of ethanol is 20%~30%, and the rest is water; the mass volume fraction of calcium chloride in the dissolving agent composed of calcium chloride and formic acid is 5%~8%.
[0025] In this example, the effects of the mass fractions of calcium chloride and ethanol on the dissolution rate of silk fibroin were verified in turn. First, the effect of the mass fraction of calcium chloride on the dissolution rate of silk fibroin was verified. 1 g of degummed silk was added into 5 mL of a solvent consisting of calcium chloride, ethanol and water to dissolve the silk fibroin. The temperature of the solvent was set at 70 °C. o C, and the mass fraction of calcium chloride was adjusted successively. When there was no silk fibroin fiber remaining in the solution, it was completely dissolved. The time for the silk fibroin to be completely dissolved was observed and recorded every 30 min. The dissolution results are shown in Table 1.
[0026] Table 1 Effect of calcium chloride content on the dissolution rate of silk fibroin
[0027] The content of calcium chloride affects the dissolution rate of silk fibroin. High concentrations of calcium ions can destroy hydrogen bonds and van der Waals forces in silk fibroin and accelerate dissolution. The results in Table 1 show that increasing the calcium chloride content to 30% can significantly accelerate the dissolution of silk fibroin, and the dissolution efficiency of 50% is not significantly improved compared to 40%. Therefore, the mass fraction of calcium chloride is selected to be 30%~40%.
[0028] Secondly, the effect of ethanol mass fraction on the dissolution rate of silk fibroin was verified. 1 g of degummed silk was added into 5 mL of a solvent consisting of calcium chloride, ethanol and water and dissolved. The temperature of the solvent was set at 70 o C, the ethanol mass fraction was adjusted until there was no silk fibroin fiber residue in the solution, which was a completely dissolved state. The time for the silk fibroin to be completely dissolved was observed and recorded every 30 min. The dissolution results are shown in Table 2.
[0029] Table 2 Effect of ethanol content on the dissolution rate of silk fibroin
[0030] The content of ethanol affects the dissolution rate of silk fibroin. Ethanol can infiltrate silk fibroin molecules, accelerate the penetration of calcium ions, and accelerate dissolution. The results in Table 2 show that increasing the ethanol content to 20% can significantly accelerate the dissolution of silk fibroin, and the dissolution efficiency of 40% is not significantly improved compared to 30%. Therefore, the mass fraction of calcium chloride is selected to be 20%~30%.
[0031] In some embodiments, the dissolution temperature is 60-90° C., and the dissolution time is 2-5 hours.
[0032] In this example, the effect of dissolution temperature on the dissolution rate of silk fibroin was verified. 1 g of degummed silk was added into 5 mL of a solvent consisting of 30% by mass calcium chloride, 20% by mass ethanol and 50% by mass water to dissolve. The dissolution temperature was adjusted until no silk fibroin fibers remained in the solution, indicating a completely dissolved state. The time it took for the silk fibroin to be completely dissolved was observed and recorded every 30 minutes. The dissolution results are shown in Table 3.
[0033] Table 3 Effect of temperature on the dissolution rate of silk fibroin
[0034] Increasing the temperature can intensify molecular motion and accelerate dissolution. The results in Table 3 show that 60 o C. The dissolution rate of silk fibroin begins to increase. Therefore, the dissolution temperature is selected to be 60 o C ~ 90 o C.
[0035] In some embodiments, the molecular weight cutoff of the dialysis bag used for dialysis is greater than 10KDa, the number of dialysis is 3 to 9 times, and the duration of each dialysis is 2 to 4 hours.
[0036] In this example, the effect of the number of dialysis on the calcium ion concentration in the silk fibroin solution was verified. 1 g of degummed silk was dissolved in 5 mL of a solvent consisting of 30% calcium chloride, 20% ethanol and 50% water by mass. The dissolution temperature was fixed at 70 degrees. The solution was transferred to a dialysis bag with a molecular weight cutoff of 10 kDa for dialysis. The silk fibroin solutions of the 3rd, 5th, 7th and 9th dialysis were collected and the calcium ion concentration was detected by an inductively coupled plasma spectrometer. The calcium ion concentration results can be referred to Figure 2 , the calcium ion concentration decreases with the increase of dialysis times. After 7 dialysis times, the decrease of calcium ion concentration slows down significantly. In addition, the ethanol residue in the first 2 dialysis times is high and is not considered. Therefore, 3 to 7 dialysis times are selected.
[0037] In some specific embodiments, the effect of calcium ion concentration on the gelation time of silk fibroin aqueous solution was further verified. 1 g of degummed silk was added into 5 mL of a solvent consisting of 30% by mass of calcium chloride, 20% by mass of ethanol and 50% by mass of water to dissolve the silk. The dissolution temperature was fixed at 70 degrees. The silk fibroin solution was transferred to a dialysis bag with a molecular weight cutoff of 10 kDa for dialysis. The silk fibroin solutions of the 3rd, 5th, 7th and 9th dialysis were collected and 1% silk fibroin solution was prepared for high-speed rotation emulsification at a speed of 8000 rpm for 1 min and 40 o C was used to prepare silk fibroin gel, and the gelation was observed every 30 min. The effect of calcium ion concentration on the gelation time of silk fibroin can be found in Figure 3 Calcium ions can chelate and cross-link the hydrophilic chains of silk fibroin and accelerate the gelation rate. Figure 2 Results: Reducing the number of dialysis times and increasing the calcium ion content are beneficial to accelerating the gelation of silk fibroin.
[0038] In some embodiments, before S3, the silk fibroin solution is diluted or concentrated to adjust the concentration to 0.1-10.0 wt %. The dilution method includes diluting with water, and the concentration method includes ultrafiltration, PEG solution dialysis or heating volatilization.
[0039] In some embodiments, the shear force is applied by an emulsifier, and the emulsifier can drive the silk fibroin solution to rotate. The rotation speed of the emulsifier is 8000~30000rmp, the rotation time is 30s~5min, the incubation temperature is 40~80℃, and the incubation time for gelation is 0.5~3h.
[0040] In this embodiment, the effect of the speed, rotation time and incubation temperature of the emulsifier on the gelation time of silk fibroin was verified. 1 g of degummed silk was added to 5 mL of a solvent consisting of 30% calcium chloride, 20% ethanol and 50% water by mass, and the dissolution temperature was fixed at 70 degrees. The silk fibroin egg was transferred to a dialysis bag with a molecular weight cutoff of 10 kDa and dialyzed 7 times. A 1% silk fibroin solution was prepared for high-speed rotation emulsification, and the speed, time and incubation temperature were adjusted to prepare silk fibroin gel. The gelation was observed every 30 min. The results of the effect of the speed, time and incubation temperature on the gelation time of silk fibroin are shown in Tables 4, 5 and 6.
[0041] Table 4 Effect of rotation speed on the gelation rate of silk fibroin
[0042] Table 5 Effect of emulsification time on the gelation rate of silk fibroin
[0043] Table 6 Effect of incubation temperature on the gelation rate of silk fibroin
[0044] refer to Figure 4 , the effect diagram of silk fibroin solution and silk fibroin gel, silk fibroin forms β-fold cross-linking under high shear force, and its gelation time is shortened with the increase of emulsification speed, emulsification time and incubation temperature. According to the test results, the speed range can be 8000~30000 rpm, the duration can be 30 s~5 min, and the incubation temperature can be 40~80 o C is used to gel the silk fibroin aqueous solution.
[0045] The above is only a specific implementation of the embodiment of the present application, but the protection scope of the embodiment of the present application is not limited thereto, and any changes or replacements within the technical scope disclosed in the embodiment of the present application should be included in the protection scope of the embodiment of the present application. Therefore, the protection scope of the embodiment of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a silk fibroin hydrogel containing divalent bioactive metal ions, characterized in that: The following steps are involved: S1: dissolving the degummed silk with a solvent to prepare a silk fibroin stock solution; S2: dialyzing the silk fibroin stock solution in water dissolved with a divalent metal salt to obtain a silk fibroin composite solution; S3: After heat treatment, the silk fibroin composite solution is subjected to shear force, and incubated to obtain a silk fibroin hydrogel containing metal ions.
2. The method for preparing silk fibroin hydrogel according to claim 1, characterized in that: In said S1: The dissolving agent includes calcium chloride, ethanol and water, or the dissolving agent includes calcium chloride and formic acid solution; The mass fraction of calcium chloride in the dissolving agent composed of calcium chloride, ethanol and water is 30% to 40%, the mass fraction of ethanol is 20% to 30%, and the rest is water; In the dissolving agent composed of calcium chloride and formic acid, the mass volume ratio of calcium chloride in the formic acid solution is 5% to 8%.
3. The method for preparing the silk fibroin hydrogel according to claim 2, characterized in that: In S1: The dissolution temperature is 60-90° C., and the dissolution time is 2-5 hours.
4. The method for preparing the silk fibroin hydrogel according to claim 1, characterized in that: In S2: The molecular weight cutoff of the dialysis bag used for dialysis is greater than 10KDa, the number of dialysis is 3 to 9 times, and the time of each dialysis is 2 to 4 hours.
5. The method for preparing the silk fibroin hydrogel according to claim 1, characterized in that: In S2: the divalent metal salt refers to a water-soluble divalent metal salt that is soluble in water, and the divalent metal salt includes magnesium, zinc, calcium, copper, strontium and iron.
6. The method for preparing the silk fibroin hydrogel according to claim 1, characterized in that: Before the S3 includes: The silk fibroin solution is diluted or concentrated to adjust the concentration to 0.1-10.0 wt %.
7. The method for preparing the silk fibroin hydrogel according to claim 6, characterized in that: The dilution method includes dilution by adding water; The concentration method includes ultrafiltration, PEG solution dialysis or heating volatilization.
8. The method for preparing the silk fibroin hydrogel according to claim 1, characterized in that: In the S3: The shear force is applied by an emulsifier, and the emulsifier can drive the silk fibroin solution to rotate.
9. The method for preparing the silk fibroin hydrogel according to claim 8, characterized in that: The rotation speed of the emulsifier is 8000-30000 rpm, and the rotation time is 30 s-5 min.
10. The method for preparing the silk fibroin hydrogel according to claim 1, characterized in that: In the S3: The incubation temperature is 40-80° C., and the incubation time for gelation is 0.5-3 h.
11. A silk fibroin hydrogel containing divalent bioactive metal ions, characterized in that: The method is prepared by any one of claims 1 to 10.
Citation Information
Patent Citations
Preparation method and application of injectable silk fibroin in-situ gel
CN103289107A
Rapid preparation method of silk fibroin protein gel
CN106866996A
Silk fibroin hydrogel for treatment of intrauterine adhesion
CN110064077A
Silk fibroin hydrogel dressing as well as preparation method and application thereof
CN115282324A
Cited By
Bionic regenerated silk protein multifunctional hydrogel suture line as well as preparation method and application thereof
CN120695241A
A biomimetic regenerated silk protein multifunctional hydrogel suture, its preparation method and application
CN120695241B